PENGARUH PENDEKATAN EKSPRESIF DALAM CERPEN “ROBOHNYA SURAU KAMI” KARYA AA NAVIS SEBAGAI PEMAHAMAN KARAKTER CERPEN - Santi Faujiah; Andra Muhammad Rizky (Populer: Jurnal Penelitian Mahasiswa, 2022)
This study aims to find and analyze the intrinsic elements contained in the short story "Robohnya Surau Kami" by AA Navis. This research was conducted within the scope of the field of literature and was carried out using qualitative methods and descriptive data analysis techniques. In this research, it is necessary to study documents and study literature. In the world of education, the teacher's role is not only AS a provider of material, but also AS an educator who teaches character for each student. Educators AS examples and reflections in the world of education that teach how to shape students with character. One way to shape the character of students is through a literary work. Literary work is something that is conveyed communicatively both orally and in writing in which there is a message or intention to be conveyed by the author. Through literary works students can easily understand how to build a good character in everyday life, because literary works are also a reflection of life. There are many theories and literary approaches to studying a literary work. One of them is the expressive approach. Through an expressive approach students can recognize the characters in a literary work. One of them is in a short story literary work entitled "Robohnya Surau Kami".